1987
DOI: 10.1007/bf01852085
|View full text |Cite
|
Sign up to set email alerts
|

Influence of buprenorphine on acute experimental pancreatitis

Abstract: Buprenorphine (15 micrograms/kg b.wt. per hour) distinctly reduced pain sensitivity in acute 3% sodium-taurocholate pancreatitis in male Wistar rats without interfering with the course of the disease. This was seen by assessment of enzyme elevation in serum and ascites and by histological evaluation of the pancreas. Buprenorphine is therefore recommended for animal experiments to study the effect of therapeutic principles in acute pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…A argument used frequently in opposition to providing pain medication in models like the pancreatitis model is the fear of affecting inflammatory processes and therefore the read-out parameters ( Stumpf et al, 2016 ). Data on these effects is still contradictory, several papers report either negative or absent influence of analgesics ( Wereszczyñska-Siemiatkowska et al, 1987 ; Ogden et al, 1994 ; Kim et al, 2004 ; Bai et al, 2012 ; Stumpf et al, 2016 ; Barlass et al, 2018 ). Moreover, the effect of the same analgesic, in this case, Rofecoxib, can differ between species ( Reding et al, 2006 ; Silva et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A argument used frequently in opposition to providing pain medication in models like the pancreatitis model is the fear of affecting inflammatory processes and therefore the read-out parameters ( Stumpf et al, 2016 ). Data on these effects is still contradictory, several papers report either negative or absent influence of analgesics ( Wereszczyñska-Siemiatkowska et al, 1987 ; Ogden et al, 1994 ; Kim et al, 2004 ; Bai et al, 2012 ; Stumpf et al, 2016 ; Barlass et al, 2018 ). Moreover, the effect of the same analgesic, in this case, Rofecoxib, can differ between species ( Reding et al, 2006 ; Silva et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Barlass et al showed that morphine increases acute pancreatitis and reduces regeneration in mice ( Barlass et al, 2018 ). Buprenorphine applied in rats is reported to either reduce or not influence pancreatitis ( Wereszczyñska-Siemiatkowska et al, 1987 ; Ogden et al, 1994 ; Kim et al, 2004 ). The previously mentioned study by Stumpf et al indicated that Metamizole does not influence acute pancreatitis in mice ( Stumpf et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study about the in uence of buprenorphine on acute experimental (3% sodium taurocholate induced) pancreatitis showed a distinct reduction of pain without interfering with the course of pancreatitis (14).…”
Section: Discussionmentioning
confidence: 99%
“…All animals received an intermittent subcutaneous infusion of saline (80 ml/kg/day) for the rst 24 h in order to counteract postpancreatitis hypovolaemia (20,21). Buprenorphine (0.03 mg/ kg) was given subcutaneously every 12 h during the experiment as an analgesic (22,23). Food and water were provided ad libitum.…”
Section: Pancreatitis Modelmentioning
confidence: 99%